Construction of a Nanostructured Stabilization System for Sea Cucumber Lipids and Their Precise Intestinal Release Mechanism (Journal of the European Academy Open University, 2026)
The annual output of sea cucumber processing by-products in China exceeds 100,000 tons, which are rich in functional lipids such as cerebrosides and EPA/DHA, making them a valuable resource for high-value utilization. However, disadvantages such as the easy oxidation of sea cucumber lipids, intolerance in the gastrointestinal tract, and lack of targeting seriously affect their efficacy. Using sea cucumber processing by-products as raw materials, this paper starts from three aspects: nanostructured stabilization construction, targeted intestinal delivery, and precise release mechanisms. It elaborates on the green and highly efficient preparation of sea cucumber lipids, the triple stabilization system of protein self-assembly, liposomes, and hydrogels, and the pH-enzyme dual-responsive precise release pathway. It reveals the structure-activity relationship and in vivo transport laws, providing a theoretical basis and technical route for the high-value utilization of sea cucumber functional lipids and the creation of novel special dietary foods.